2020
DOI: 10.18203/2320-1770.ijrcog20203827
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hyperemesis gravidarum and associated risk factors among pregnant women in a tertiary health facility in Northeast, Nigeria

Abstract: Background: One of the commonest symptoms observed in pregnant women before the 20th week of gestation is nausea and vomiting, an exaggeration of these symptoms hyperemesis gravidarum (HEG) could result in maternal and fetal catastrophes and even death. The objective of this study was to determine the prevalence and associated risk factors for hyperemesis gravidarum among pregnant women at booking.Methods: A prospective institutional based study design was done among 452 pregnant women seen at booking in a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
2
7
2
Order By: Relevance
“…Pregnant women who live in rural areas are of poor socioeconomic status and are exposed to stress that increases the severity of nausea and vomiting. While this finding was lower than the study conducted in North-East Nigeria (44.9%) [ 8 ]. This difference might be due to differences in study design and study population.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Pregnant women who live in rural areas are of poor socioeconomic status and are exposed to stress that increases the severity of nausea and vomiting. While this finding was lower than the study conducted in North-East Nigeria (44.9%) [ 8 ]. This difference might be due to differences in study design and study population.…”
Section: Discussioncontrasting
confidence: 80%
“…In the world, Asian and Middle Eastern ethnicities have higher rates of HG, even as high as 10.8% in a study reported by Fejzo et al [ 6 ]. In Africa, studies conducted in Egypt and Northeast Nigeria revealed that the proportion of HG was 4.5% and 44.9% respectively [ 7 , 8 ]. Studies conducted in Ethiopia Jimma university hospital, Addis Ababa three teaching hospitals and Arba Minch General Hospital stated that the proportion of HG was 4.8%, 4.4% and 8.2% respectively [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a review article by Gabra A in 2018 found that there was a strong association between family history and HEG [ 1 ]. This finding is also similar to a study done in Uganda, Nigeria, and the USA [ 3 , 21 , 24 ], which shows a significantly higher risk of hyperemesis in women whose sister’s or mother’s had hyperemesis gravidarum. This could be because of the familial aggregation gene, mainly the growth differentiation factor 15 gene and its action in the chemoreceptor trigger zone of the brain which has genetic associations with HEG.…”
Section: Discussionsupporting
confidence: 91%
“…However, this contradicts a study done in Nigeria, in which multiparity was a risk factor. The possible explanation given in this study is that most women in the study included were above the age of 30; in this age group, women might have had two or more deliveries because of the cultural practice of early marriage and childbearing in Nigeria [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by a study conducted in northern Ethiopia, southern Ethiopia, and a study done in Nigeria. 13 , 21 This is the fact that the genetic predisposition to the condition, evidence supports that daughter women who experienced the condition were at increased risk of developing HG. Family-based studies provide evidence that female relatives of patients with HG are more likely to be affected, with a 17-fold increased risk if a sister has HG.…”
Section: Discussionmentioning
confidence: 96%